Artificial Intelligence, Smart Robots, Types of Artificial Intelligence and a New Economic Order - Sitki Selim Dolanay (An Overview on Business, Management and Economics Research Vol. 2, 2023)
In the process of transition from agricultural society to industrial society, which started with the Industrial Revolution in England, the mechanization process experienced five different stages and in the last stage, with the development of computers, automation in production was achieved. While developments in a certain region or country of the world spread to other parts of the world with technological spread, technological revolutions also spread and paradigm changes occurred. With the development of information processing technologies, productivity has started to increase with the use of automation and robot technology in production. This process, which continued until the 2010s, is thought to lead to the formation of smart factories that can produce under the dominance of robots, after the new point reached in artificial intelligence and robot technology, and this development will further increase productivity in production. Intelligent robots working in the internet of things system will be able to work with greater power and longer periods than humans, and smart factories that are almost never shut down will emerge. In the transformation in this process, which is also called robonomics, changes in the theory of economy may occur and a new economic order may emerge. The question of why behind-the-scenes countries, such as Turkey, could not catch up with the leading ones, is another matter of discussion. However, in such periods of technological paradigm change, an opportunity arises for lagging countries for their economic development. On the other hand, we can say that Turkey will either be able to catch up with the technological level of developed countries by taking advantage of the opportunity, by means of a step-by-step technological development, or it will continue to stay among the countries that lag behind by missing the opportunity.